Inclusive Education - Lambert, Lukischa (Journal of the American Academy of Special Education Professionals, 2008)
The placement and education of students with disabilities in the general education classroom has generated a challenge and varied opinions for educators, families, and service providers. It is likely that with recent litigation and legislation which supports inclusion and increasing pressure from advocates of inclusion, the trend towards including students with disabilities in the general education classroom will continue. Classroom teachers’ and administrators’ perceptions along with students’ self-perceptions must be considered as these may have a great impact on the inclusion of students with disabilities in general education settings. The purpose of this paper is to address concerns and give helpful strategies for inclusive education.